Religious Moderation of Muslim and Buddhist communities to realizing interfaith harmony in Veteran Street, East Banjarmasin - Rosyida Nurul Anwar; Noor Ainah; Mochamad Iqbal Abdul Ghoni (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
Muslims and Buddhists, as fellow believers, have the potential to support each other and establish mutually beneficial and productive relationships in building society, nation and state. The portrait of diversity, harmony, and religious tolerance in Indonesia is reflected in Veteran Street, East Banjarmasin District. The study aimed to analyze religious moderation in Muslim and Buddhist communities in realizing harmony between religious communities. The study used a qualitative approach with a naturalistic phenomenology type. Data collection used observation, interview, and documentation techniques. The study resulted in 1) religious moderation of Muslim and Buddhist communities in realizing harmony between religious communities through long-standing interactions between Muslim and Buddhist communities; 2) the existence of social cooperation in the form of interfaith social services; 3) the absence of conflict in society manifests the existence of tolerance; 4) the existence of a national commitment by upholding democratic attitudes and national values; 5) participation in religious activities is shown by sharing happiness in essential moments of Islam and Buddhism; 6) the existence of humanity by showing high empathy towards each other. Harmony between moderate religions, which is the goal of moderate attitudes, needs to be preserved and become a habit for all religious communities.